Signifying the relationship between education input, social security expenditure, and urban-rural income gap in the circular economy - Wang, Yuan; Huang, Yingjun; Sarfraz, Muddassar (Frontiers in Environmental Science, 2022)
This paper takes the inter-provincial panel data of China from 1999 to 2015 as the research sample and uses the GMM estimation method to empirically test the relationship among education input, social security expenditure, and urban-rural income gap. The results show that education input and social security expenditure have a significant impact on the urban-rural income gap, and there are regional differences. Specifically, the augments of education input and social security expenditure widens the urban-rural income gap in the western region, and narrows the urban-rural income gap of the eastern and central regions but has less impact on the eastern region. The paper provides a new perspective for understanding the urban-rural income gap in China, and has a significance meaning for further increasing the educational investment in the western rural areas, and improving the redistribution efficiency of social security expenditure.